EFFECT OF ANTANAN (CENTELLA ASIATICA) AND VITAMIN C ON THE BURSA OF FABRICIUS, LIVER MALONALDEHIDE AND PERFORMANCE OF HEAT-STRESSED BROILERS - SUTARDI, TOHA; KUSNADI, ENGKUS; WlDJAJAKUSUMA, REVIANY (BIOTROPIA, 2011)
High environmental temperatures may cause heat stress in poultry. This may increase water consumption, decrease feed consumption and in rum, decrease productivity level. In addition, high temperature contributes to oxidative stress, a condition where oxidant activity (free radicals) exceeds antioxidant activity. In our research, antanan (Centelta asiatica) and vitamin C were utilized as anti heat-stress agents for heat-stressed broilers. We used 120 male broilers 2 - 6 weeks old, kept at 31.98 ± 1.94 °C during the day and 27.36 ± 1.31 °C at night. The data collected were analyzed with a completely randomized factorial design of 2 x 3 (2 levels of vitamin C, 3 levels of antanan at 4 replications) and continued with the contrast-orthogonal test when significantly different. The results indicate that the treatments of 5 and 10% of antanan with or without 500 ppm of vitamin C and vitamin C alone significantly (P<0.05) decreased the heterophil/lymphocyte (H/L) ratio and liver malonaldchydc (MDA). These treatments, however, significantly (P<0.05) increased the bursa of Fabricius weight, feed consumption and body weight gain. It could be concluded that basal ration administered with 5% antanan and 500 ppm vitamin C could effectively prevent broilers from heat stress. The results support the conclusion that a basal ration supplemented with 5% antanan and 500 ppm of vitamin C or their combinations, effectivelly reduces heat stress in broilers. Key words : Heat stress/ Centella asiatica I Vitamin C